2013
DOI: 10.3389/fonc.2013.00077
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery and Stereotactic Body Radiation Therapy Cost-Effectiveness Results

Abstract: Objective: To describe and synthesize the current stereotactic radiosurgery (SRS) and stereotactic body radiation therapy (SBRT) cost-effectiveness research to date across several common SRS and SBRT applications.Methods: This review was limited to comparative economic evaluations of SRS, SBRT, and alternative treatments (e.g., other radiotherapy techniques or surgery). Based on PubMed searches using the terms, “stereotactic,” “SRS,” “stereotactic radiotherapy,” “stereotactic body radiotherapy,” “SBRT,” “stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…The relative cost-effectiveness of SBRT is an issue. [132][133][134][135] Clearly, the conclusion depends on the technique to which is SBRT is compared. For example, in spinal SBRT a single 8-Gy fraction delivered via 2 opposed fields will clearly have a lower treatment cost than SBRT.…”
Section: Future Effortsmentioning
confidence: 99%
“…The relative cost-effectiveness of SBRT is an issue. [132][133][134][135] Clearly, the conclusion depends on the technique to which is SBRT is compared. For example, in spinal SBRT a single 8-Gy fraction delivered via 2 opposed fields will clearly have a lower treatment cost than SBRT.…”
Section: Future Effortsmentioning
confidence: 99%
“…Despite these encouraging results, to date there are no phase III studies available to define the role of SBRT for bone metastases compared to conventional radiation techniques. Moreover, according to cos‐effectiveness studies, SBRT provides similar efficacy with EBRT, but with a higher cost (Bijlani, Aguzzi, Schaal & Romanelli, ; Haley et al., ). The latter emerge the necessity of targeting patients which may most benefit by the SBRT.…”
Section: Discussion – Conclusionmentioning
confidence: 99%
“…Nevertheless, many studies have concluded that SBRT is cost effective, as it allows a better organ sparing and dose escalation on the target volume, and they are also cost saving. [19][20][21] Although SBRT in PC could not be considered yet a standard option, due to the small number of patients treated worldwide and the relatively short follow-up of most of the published experiences, its preliminary results are promising and SBRT adoption is rapidly increasing in the radiation oncology departments. 1, 18,22 Moreover, technological innovations should not replace the clinical aspects of PC, and indications for SBRT should be reserved to those patients who would really benefit from this treatment.…”
Section: Modern Stereotactic Body Rt: the Technology Revolutionmentioning
confidence: 99%